'Do you mean besides researching and studying?' Finnish teacher educators' views on their professional development. Issue 1 (1st January 2020) - Maaranen, Katriina; Kynäslahti, Heikki; Byman, Reijo; Sintonen, Sara; Jyrhämä, Riitta
ABSTRACT: Professional development of teacher educators has not been researched very much in Finland, although interest in teacher educators has started to increase globally in recent decades. This study investigates 15 Finnish teacher educators' views on their professional development. The results indicate that research plays a significant role in the Finnish teacher educators' conceptions. They considered research to be an integral part of their work, as it is part of their assigned tasks. This differs from many countries, where researching and high-quality scientific contribution is not necessarily a big part of teacher educators' work. These teacher educators also viewed research as a means to develop professionally, both through producing and consuming research. Formal professional development, such as professional development courses, did not play a significant role for these teacher educators, though studying either by reading research or participating in free-time education seemed to be more important. The results also indicate that Finnish teacher educators are under pressure to produce high-quality research and to advance in their careers. This is due to business ideology in leadership, i.e. management by results in the Finnish university sector.